NON TRANSPARENT DISCRIMINATION OF CONTRACTUAL FACULTY VIA POLICIES IN ENGINEERING COLLEGES OF SAARC NATION LIKE INDIA - Vishal Mahajan, Pradeep Kumar Varshney, Darshan Kumar (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
The examination plans to evaluate job satisfaction and human rights for contract personnel working in government and private outlining establishments orchestrated in nation zone of area Gurdaspur (Punjab) India. It basically revolves around the diverse partition approaches executed by colleges administration towards the contract personnel and how they are abusing these faculty in the midst of their calling with the help of these courses of action. The examination incorporates 150 contract staff who responded to a survey intended to evaluate the variety of Job Satisfaction level. It is dissected that staff of the considerable number of establishments had a modest movement satisfaction level. Additionally, result speaks to the activity fulfillment level changes as for sexual orientation, teaching experience, and academic status (designation). With the help of SPSS-16 programming all the logical results of the examination have been checked.